2019
DOI: 10.1590/1980-265x-tce-2018-0221
|View full text |Cite
|
Sign up to set email alerts
|

Technologies for Health Education for the Deaf: Integrative Review

Abstract: Objective: investigate the scientific evidence on the technologies that are used for health education for deaf people. Method: integrative review carried out in October 2017, with the publications of the last 15 years, in the databases MEDLINE/PubMed, CINAHL, LILACS via Biblioteca Virtual em Saúde (BVS), Web of Science and Scopus. Results: we found 3367 articles, of which 19 were included in the study. The predominant type of technology was video, present in ten studies and computerized technologies, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
(19 reference statements)
0
5
0
9
Order By: Relevance
“…The lesser use of subtitles is relevant, as the textual understanding of deaf people is not the same as that of listeners. Although there are literate deaf people, depending on the size and form of writing the text, it is common to have difficulty understanding, so the use of subtitles, in videos for deaf people, should occur with caution (23) . This context is corroborated by a study carried out in Malaysia, in which deaf people participated in the creation of an application, demonstrating that they do not prefer the presence of texts in the presentation of the content of the technology (24) .…”
Section: Discussionmentioning
confidence: 99%
“…The lesser use of subtitles is relevant, as the textual understanding of deaf people is not the same as that of listeners. Although there are literate deaf people, depending on the size and form of writing the text, it is common to have difficulty understanding, so the use of subtitles, in videos for deaf people, should occur with caution (23) . This context is corroborated by a study carried out in Malaysia, in which deaf people participated in the creation of an application, demonstrating that they do not prefer the presence of texts in the presentation of the content of the technology (24) .…”
Section: Discussionmentioning
confidence: 99%
“…This model for recruiting participants for research demonstrates that, over time, the research groups develop new methods, models and theories with the support of telecommunications, in order to enhance the infrastructure already available, aiming at new applications and services. [3][4][5][6][7][8][9][10] The supporting software programs for data analysis can be described as a research data management strategy, as they exercise the function of systematically and quickly organizing data storage, management and recovery. Although the software programs are important for these processes, the analytical capacity of the researcher is indispensable to conduct analytical thinking and scientific research.…”
Section: Discussionmentioning
confidence: 99%
“…4 The previous literature on the content suggests research studies that address the theme of technology in various themes and specialties in the health area, comparing the use of more than one technological resource and evaluating the primary and secondary outcomes of the technologies used in education in the long run. 5 However, studies specifically related to the adoption of Information and Communication Technologies in the management of Nursing research groups were not identified.…”
Section: Introductionmentioning
confidence: 99%
“…Dentre as tecnologias educativas descritas na literatura, com a finalidade de ofertar cuidados baseado em resultados eficazes, destaca-se o vídeo educativo, como uma ferramenta mais utilizada por esta população, devido à sua dinamicidade, apresentando benefícios no processo de ensino-aprendizagem (9) . Assim, com o intuito de enfocar as relações inter e intrapessoais numa perspectiva positiva da deficiência, a fim de transmitir conteúdo com equidade de informação, esse estudo fundamentou-se na Teoria da Aprendizagem proposta por Vigotski.…”
Section: Introductionunclassified